A new species of Rheumatobates Bergroth (Hemiptera: Heteroptera: Gerridae) from mangroves of the Colombian Caribbean region, new records, and a key to species recorded from the country - Molano, Fredy; Mondragón, Silvia P.; Morales, Irina (Zootaxa, 2017)
Rheumatobates urabaensis sp. nov. (Gerridae: Rhagadotarsinae) is described from a mangrove of the Colombian Caribbean region. R. urabaensis sp. nov. is differentiated from other species of the genus by features of the male antennae, fore legs, and genitalia. New distribution records are presented for R. bergrothi Meinert, R. crassifemur esakii Schroeder, and R. spinosus Hungerford. A key to the species of Rheumatobates from Colombia is also provided.